Upaya Pemanfaatan Digitalisasi Marketing dalam Meningkatkan Penjualan UMKM Kecamatan Kradenan - Diana Indah Sari; Nugraeni Nugraeni (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Using digital marketing to increase sales of MSMEs, digital marketing has a very important role in increasing sales and income so they can access a wider market. Lack of understanding, skills and abilities in using digital technology is one of the obstacles experienced by MSME players. In this problem, the way to overcome the problems faced by MSME players is that training is provided on how to use digital applications, especially the WhatsApp business and Instagram applications to improve the abilities and skills of MSME players in using digital as a promotional media. The method used in this field work activity uses direct mentoring and training methods for MSME actors by implementing the stages of observation, interviews, planning, activities, activity processes, end of activities, and documentation. With the results, MSME players have begun to understand and understand how to manage and use the WhatsApp business and Instagram applications as media for promoting online sales of the goods they produce.